A new approach to weak convergence of random cones and polytopes - Kabluchko, Zakhar; Temesvari, Daniel; Thäle, Christoph (Canadian journal of mathematics, 2021)
A new approach to prove weak convergence of random polytopes on the space of compact convex sets is presented. This is used to show that the profile of the rescaled Schläfli random cone of a random conical tessellation, generated by n independent and uniformly distributed random linear hyperplanes in $\mathbb {R}^{d+1}$ , weakly converges to the typical cell of a stationary and isotropic Poisson hyperplane tessellation in $\mathbb {R}^d$ , as $n→ ∞ $ .